Impact of resistance training on biokinetic abilities, functional variables, and the skill of free-throw shooting in female basketball players - Ne’ma Kadhim, Evan; Mizher Abboud, Naseer (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to evaluate the impact of resistance training on biokinetic abilities, functional variables, and the skill of free-throw shooting in female basketball players. The research method utilized by the two researchers was the experimental method, specifically employing a one-group design. The research sample was selected using a random method, with 12 players chosen to represent the college basketball team. The following tests were employed: tests for biokinetic abilities, functional tests and tests of offensive basketball skills. SPSS was utilized to statistically analyze the data. The results showed that resistance training positively impacted the development of basketball free-throw skills by accelerating the development process and enhancing shooting focus. Also, this training method played a significant role in enhancing the biokinetic capabilities of the female basketball players, through diverse exercise volume and repetition. Finally, the use of resistance training effectively enhanced the studied functional variables in the research sample, by promoting functional adaptation through exercise repetition and variation.